Socio-economic Effects of Organic Certification of Nepalese Orthodox Tea - Mishra, P.; Kattel, R. R. (Journal of Agriculture and Environment, 2021)
Organic certified orthodox tea production has high potential of improving agrarian livelihoods, environmental sustainability, and export markets. There has been limited study on economic benefits and social impact of certified orthodox tea production. This study was conducted to identify such impacts in Ilam district of Nepal. Primary data were collected through a pre-tested semi-structural interview schedule by using Kobo Toolbox, Direct Observation, Focus Group Discussions and Key Informant, and secondary data from journals, articles, bulletin, and reports from different organizations. Data were analyzed using economic, and social-related variables in a multiple regression model to identify whether the organic certification contributed to higher household income. The study revealed that price premium received by farmers for organic certified orthodox tea was almost 1.7 times of that received for organic non-certified orthodox tea. Despite higher price available, B/C ratio in case of organic certified growers is not significantly different from that of non-certified orthodox tea growers due to extra labor input and lower yield in certified production. Certified orthodox tea growers have a guaranteed market to sell their products to contracted tea processing factories. Moreover, non-certified growers were also facing problems in credit access and due to low product marketability and selling price as well as insect pests and diseases. Hence, policy focuses on promoting organic certification and increasing yield in organic certified orthodox tea plantations are appreciative.